Structure optimization of high indium content InGaAs/InP heterostructure for the growth of In（0.82）Ga（0.18）As buffer layer - 魏秋林 郭作兴 赵磊 赵亮 袁德增 缪国庆 夏茂盛 (光电子快报：英文版, 2016)
Microstructure and misfit dislocation behavior in InxGa（1-x）As/InP heteroepitaxial materials grown by low pressure metal organic chemical vapor deposition（LP-MOCVD） were analyzed by high resolution transmission electron microscopy（HRTEM）, scanning electron microscopy（SEM）, atomic force microscopy（AFM）, Raman spectroscopy and Hall effect measurements. To optimize the structure of In（0.82）Ga（0.18）As/InP heterostructure, the InxGa（1-x）As buffer layer was grown. The residual strain of the In（0.82）Ga（0.18）As epitaxial layer was calculated. Further, the periodic growth pattern of the misfit dislocation at the interface was discovered and verified. Then the effects of misfit dislocation on the surface morphology and microstructure of the material were studied. It is found that the misfit dislocation of high indium（In） content In（0.82）Ga（0.18）As epitaxial layer has significant influence on the carrier concentration.